2013
DOI: 10.4238/2013.december.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for inbreeding depression in the tree Robinia pseudoacacia L. (Fabaceae)

Abstract: ABSTRACT. The magnitude of inbreeding depression within populations is important for the evolution and maintenance of mixed mating systems. However, data are sparse on the magnitude of inbreeding depression in Robinia pseudoacacia. In this study, we compared differences in the mature seed set per fruit, seed mass, germination success, and seedling growth between self-and crosspollination treatments and estimated the inbreeding depression at 3 stages: seed maturation, seedling emergence, and seedling growth at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…In our previous study, progenies resulting from cross-pollination treatments showed significantly higher fitness than progenies resulting from self-pollination, which exhibit high levels of inbreeding depression. The highest inbreeding depression was observed between the fertilization and seed maturation stages, whereas the seedling emergence stage showed the second highest level of inbreeding depression29. In the present study, outcross-pollen donors produced six times more seedlings than self-pollen donors in the 1:1 pollen mixtures.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…In our previous study, progenies resulting from cross-pollination treatments showed significantly higher fitness than progenies resulting from self-pollination, which exhibit high levels of inbreeding depression. The highest inbreeding depression was observed between the fertilization and seed maturation stages, whereas the seedling emergence stage showed the second highest level of inbreeding depression29. In the present study, outcross-pollen donors produced six times more seedlings than self-pollen donors in the 1:1 pollen mixtures.…”
Section: Discussionsupporting
confidence: 42%
“…Our previous study suggested that selection resulted in an overall decrease in the level of surviving selfed progeny at each life stage (aborted stage, mature seed stage, and seedling stage). Within fruits, the stylar ends showed higher outcrossing rates than the basal ends, indicating selection based on the order of seeds within the fruit2829. These results suggest that a connection may exist between nonrandom mating and ovule position in R. pseudoacacia .…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Black locust was first introduced to China during 1877-1878, and it is currently extensively cultivated in many parts of the country (Li, 1983). This species is well adapted for growth in a wide variety of soils and environmental conditions such as salt, drought, and cold, and it is used for fuel, wood fiber, feedstock, lumber, forage, and beekeeping (Barrett et al, 1990;Sun et al, 2013;Yuan et al, 2013). Consequently, black locust is an ecologically and economically valuable species; however, data regarding its genomics and genome resources are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Black locust has considerable ecological and economic value (Keeler, 1900;Yuan et al, 2013), but there are many problems that restrict cultivation of the tree. The breeding method most commonly used for black locust depends mainly on genotypic introduction and selection, and it has made significant contributions to breeding programs.…”
Section: Introductionmentioning
confidence: 99%